r → ∞ lim ∫ 0 2 π x r cos ( x ) d x r c ∫ 0 2 π x r sin ( x ) d x = L
Find the value of π L − c , where c ∈ R , L > 0 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
how did u get the idea of the line after also.... ??? please give an insight @Kushal Patankar
Log in to reply
jensen's inequality is applied there. ∵ sin(x) si concave in (0,pi/2) it lies above the line joining (0,0) and (pi/2,1).
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Jensen's Inequality
Assume f ( r ) = ∫ 0 2 π x r sin x d x
Using integration by parts, ∫ 0 2 π x r cos x d x ∫ 0 2 π x r cos x d x = r + 1 x r + 1 cos x ∣ ∣ ∣ ∣ 0 2 π + ∫ 0 2 π r + 1 x r + 1 sin x d x = ∫ 0 2 π r + 1 x r + 1 sin x d x = r + 1 f ( r + 1 )
Thus we have,
L = lim r → ∞ ∫ 0 2 π x r cos ( x ) d x r c ∫ 0 2 π x r sin ( x ) d x = lim r → ∞ f ( r + 1 ) r c ( r + 1 ) f ( r )
Now,
f ( r ) f ( r ) also , f ( r ) f ( r ) ⇒ r + 2 r < r ( π 2 ) r + 1 f ( r ) < r + 1 r < ∫ 0 2 π x r d x < r + 1 ( 2 π ) r + 1 > ∫ 0 2 π π 2 x r + 1 d x ∵ sin x > π 2 x , ∀ x ∈ ( 0 , 2 π ) > r + 2 ( 2 π ) r + 1
Consider,
lim r → ∞ f ( r + 1 ) f ( r ) = lim r → ∞ ( r + 1 ) ( π 2 ) r + 2 f ( r + 1 ) r ( π 2 ) r + 1 f ( r ) ⋅ π r 2 ( r + 1 ) = π 2
L = r → ∞ lim r c ( r + 1 ) ⋅ f ( r + 1 ) f ( r ) = r → ∞ lim r c ( r + 1 ) ⋅ π 2
Since L > 0 ⇒ c needs to be − 1 .
Thus, L = π 2
π L − c = π ⋅ π 2 − ( − 1 ) = 3